Mockingjay - Collins, Suzanne (New York, NY : Scholastic Inc., 2014)
Katniss Everdeen, having survived the Hunger Games twice, learns she and her family and friends are in danger because the Capitol holds her responsible for the unrest and races against time to protect those she cares about and the people of District 12.
Wilson's Junior High School, September 2011
School Library Journal, October 2010
Booklist starred, August 2010
Bulletin of the Center for Children's Books starre, November 2010
Pub Weekly, August 2010
New York Times, September 2010
Keywords: Insurgency -- Fiction; Survival skills -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction; Science fiction